Description of the Quality of Life of MSM HIV Suffering Groups in Surakarta - Wahyuni, Endah Sri; Hastuti, Tri; Ramadhani, Syafira Rizqi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
There has been a significant increase in HIV cases in the MSM (men who have sex with men) group. They have a greater risk of contracting HIV than the adult male group in general, which is 22x more likely to contract HIV. This is caused by risky sexual behavior, changing partners without using a condom. HIV infections in the MSM group have increased, 25.8% from 2012 to 2016. The dual stigma of sexual and status as HIV sufferers has caused them to become a hidden and difficult to reach group. This condition contributes to less than optimal handling and prevention of HIV transmission. Changes in physical, psychological and social conditions influence the productivity of PLHIV (People Living with HIV). Opportunistic infections cause physical problems. Losing their jobs, rejection and the risk of mental disorders due to their status as MSM and HIV. The high level of stigma and discrimination still hampers access to health services, thereby affecting the quality of life for PLHIV. This research aims to provide an overview of the quality of life of the MSM group suffering from HIV in Surakarta. The instrument uses a standardized questionnaire, namely the Indonesian version of WHO Quality of Life-HIV Bref which has been tested for validity and reliability. This research is a type of quantitative research using a descriptive research design with 30 respondents. The research results showed that most respondents were unmarried (86.7%), worked as private employees (66.7%), had a high school education (96.7%) and had been diagnosed with HIV for more than 5 years (63.3%). The majority of respondents' quality of life was in the sufficient category, namely 86.6%. The results of this research can be used as a reference in developing further interventions as an effort to improve the quality of life of MSM HIV in Surakarta.